Impact of Stressors on Academic Performance: A Case Study of Business Students in Karachi - , Saba Waheed; , Asif Khan; , Aqsa Ameer; , Muhammad Zair Khan; , Maristella Masi (Archives of Current Research International, 2025)
The study examines how perceived stress affects academic performance at Karachi's business schools. It tries to discover how stressors affect students' capacity to achieve academic success by looking at the particular setting of business education. This study has the potential to provide insight into tactics that can improve students' success and well-being in the challenging academic setting of Karachi's business schools. The study aims to examine the role of students' perceived stress on academic performance in the business schools of Karachi, Pakistan. The quantitative approach has been adopted for data collection, and 384 sample responses have been gathered from university students. The PLS-SEM analysis technique has been used for data analysis. The results have identified that academic load positively and significantly affects perceived stress. Financial constraints have a positive and significant effect on perceived stress. Perceived stress has a negative and significant effect on academic performance. Social support has a negative and significant effect on perceived stress. Time management has a negative but insignificant effect on perceived stress. Additionally, in this study, the factors which cause stress to students in university life are discussed. Keeping in focus this study, the practitioners should try to adopt practices which can reduce the stress level for students so that they can perform better academically and get better results. Financial constraint is considered one of the biggest reasons contributing to students' stress.